Knowledge and perceptions of traditional birth attendants treating patients with HIV/AIDS and its related stigma and discrimination in District Multan, Pakistan. - Shahzadi , Amber; Khan , Kashif Kamran (International Journal of Endorsing Health Science Research, 2022)
Background: In Pakistan, only 20% of births are attended by a competent health expert, while traditional birth attendants (TBAs) deliver 90% of births. Therefore, in Pakistan, TBAs play a dynamic role in providing maternal health. This study assessed the Knowledge and Perceptions of TBAs treating patients with HIV/AIDS and its related stigma and discrimination in district Multan, Pakistan. Methodology: A descriptive study design is used to conduct in-depth interviews and focus group discussions using a self-structured questionnaire with TBAs (FGDs = 4; n = 18) who were permanent residents. In addition, in-depth interviews (IDIs = 6) were conducted with women who had more than five years of experience and are still in practice. Participants were sampled through convenience sampling resulting in 100. Results: The results of the study indicated that TBAs have heard about HIV/AIDS, but 53.5% did not have a clear understanding of the signs and symptoms of HIV/AIDS. The knowledge of this deadly virus and disease was perceived rather vaguely by the TBAs. Most (82%) of the respondents presented a discriminatory attitude towards the people living with HIV. Conclusion: This study inferred that the targeted group was poorly informed about the actual concerns of HIV/AIDS and how to overcome stigma and discrimination. So, if we ought to cope with the hideous challenge of the pandemic and meet the 2030 goal of removing this pandemic, we are supposed to reposition and train our health care providers, especially TBAs, to meet up with the best global practices.